Arctic Images 1818-1859 - Høvik, Ingeborg (The University of Edinburgh, 2013)
This thesis asks whether there existed a unified view of the Arctic during the time period connected to the high point of British endeavour to find a Northwest Passage, from the first expeditions of the nineteenth-century in 1818 to the return of the last Franklin search party in 1859, forty-one years later. Using this time frame as its marker, the focus of the thesis is primarily on British representations of Arctic landscapes, exploration and Inuit peoples. Through careful empirical analysis of a variety of media, including professional painting, on-the-spot sketches, prints and popular exhibitions, it examines from an art historical viewpoint the historical, political, social and aesthetic contexts in which Arctic representations occurred.
Keywords: Arctic; Arctic representations; nineteenth-century; art history